Occupational UV exposure and sun-protective behaviour in German outdoor workers: results of a nationwide study - Schneider, Sven; Diehl, Katharina; Schilling, Laura; Spengler, Maria; Greinert, Rüdiger; Görig, Tatiana (Journal of occupational and environmental medicine, 2018)
Objective: The aim of the National Cancer Aid Monitoring (NCAM) was to investigate which occupational groups (1) show higher sun exposure time, (2) suffer from sunburn, and (3) use recommended protective measures. Methods: In 2016, a total of 485 individuals were classified as outdoor workers in accordance with ISCO-08 and asked about exposure time, prevalence of sunburn, and personal sun-protective measures on a sunny summer day. Results: Outdoor workers were exposed to ultraviolet (UV) radiation for a mean time of 23.6_15.3 hours per week. The 12-month prevalence of getting sunburnt at work was 19%. Only one-third of outdoor workers reported using five of the most important protective measures ‘‘often’’ or ‘‘always.’’ Conclusion: The NCAM revealed a number of high-risk groups, whose sun-protective behavior has scarcely been studied up to now.